Handbook of biometric anti-spoofing : trusted biometrics under spoofing attacks - Nixon, Mark S.; Li, Stan Z.; Marcel, Sebastien (Advances in Computer Vision and Pattern Recognition,, 2014)
As the plethora of approaches to biometrics and their deployment continues to grow, so too does the need to combat the techniques used to subvert the aim of such biometric systems. Presenting the first definitive study of the subject, this Handbook of Biometric Anti-Spoofing reviews the state of the art in covert attacks against biometric systems, and in deriving countermeasures to these attacks. Across a range of common biometrics, including face, iris, fingerprint, speaker and gait, the book describes spoofing methods and examines the vulnerabilities of biometric systems to these attacks. Novel theoretical methods are also introduced to evaluate the various possible countermeasures. Topics and features: Provides a detailed introduction to the field of biometric anti-spoofing and a thorough review of the associated literature Examines spoofing attacks against five biometric modalities, namely, fingerprints, face, iris, speaker and gait Discusses anti-spoofing measures for multi-model biometric systems Reviews evaluation methodologies, international standards, and legal and ethical issues Describes current challenges and suggests directions for future research Presents the latest work from a global selection of experts in the field, including members of the TABULA RASA project This comprehensive text/reference is truly essential reading for all biometric researchers and practitioners in industry and academia. Graduate students of computer science and electronic engineering will also find the book to be a useful supplementary reference for courses on biometrics.